The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.12659/msm.889539
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology and cost analysis of patients presented to Emergency Department following traffic accidents

Abstract: BackgroundTraffic accidents are ranked first as the cause of personal injury throughout the world. The high number of traffic accidents yielding injuries and fatalities makes them of great importance to Emergency Departments.Material/MethodsPatients admitted to Hacettepe University Faculty of Medicine Adult Emergency Department due to traffic accidents were investigated epidemiologically. Differences between groups were evaluated by Kruskall-Wallis, Mann-Whitney, and Wilcoxon tests. A value of p<0.05 was accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The average hospital stay was between 4 and 7 days among the admitted patients, which was similar to those reported by other trauma surveillance systems in Brazil (Carreiro et al 2014) and Belgrade (Bumbasirevic et al 2014). A slightly lower proportion of patients in our registry (34%) were admitted to the hospital when compared with a sample of road traffic crash injuries in Turkey (51%; Karadana et al 2013). …”
Section: Discussionmentioning
confidence: 66%
“…The average hospital stay was between 4 and 7 days among the admitted patients, which was similar to those reported by other trauma surveillance systems in Brazil (Carreiro et al 2014) and Belgrade (Bumbasirevic et al 2014). A slightly lower proportion of patients in our registry (34%) were admitted to the hospital when compared with a sample of road traffic crash injuries in Turkey (51%; Karadana et al 2013). …”
Section: Discussionmentioning
confidence: 66%
“…Trauma is more common in males in some studies in our country, but there is no information about gender in the Turkish Statistical Institute data. The reason for the increased incidence of a brain death diagnosis in males is that most accidents are accompanied by heavy head trauma [17-18].…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Furthermore, Karadanas revealed that this figure was especially high during summer (May, June, July). [ 23 ] It may be due to larger number of road trips during summer, which naturally leads to more accidents. Therefore, greater attention to roads traffic through making rules, penalties or any kind of regulation for public transportation during these risky months can help gain more control over transportation and prevent more accidents.…”
Section: Discissionmentioning
confidence: 99%